2017
DOI: 10.3390/ijerph15010037
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Solar Radiation at Different Latitudes and Pterygium: A Systematic Review of the Last 10 Years of Scientific Literature

Abstract: Pterygium is a chronic eye disease: among its recognized risk factors there is long-term exposure to ultraviolet (UV) radiation. The Sun is the main source of UV exposure: according to the World Health Organization, the Population Attributable Fraction of pterygium due to solar radiation (SR) is 42–74%. Outdoor work can deeply influence the eye exposure to solar UV rays, but, despite this, pterygium is currently not adequately considered as a possible occupational disease in this working category, at least in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 52 publications
3
37
0
1
Order By: Relevance
“…(5) In addition, ocular manifestations in port workers may be related to the handling of hazardous tools, such as chainsaws, steel cables, and containers associated with environmental factors, such as temperature, humidity, wind, fumes, pollution, and light intensity which trigger clinical ocular manifestations, such as infectious processes, photokeratitis, and pterygium. (6) Similar studies reported the same ocular manifestations. (6,7) A finding related to workers exposed to open-air, wind, and sun using dangerous working tools, as the case of port workers, showed ocular symptoms, such as blurred vision, pruritus, burning, and photophobia.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…(5) In addition, ocular manifestations in port workers may be related to the handling of hazardous tools, such as chainsaws, steel cables, and containers associated with environmental factors, such as temperature, humidity, wind, fumes, pollution, and light intensity which trigger clinical ocular manifestations, such as infectious processes, photokeratitis, and pterygium. (6) Similar studies reported the same ocular manifestations. (6,7) A finding related to workers exposed to open-air, wind, and sun using dangerous working tools, as the case of port workers, showed ocular symptoms, such as blurred vision, pruritus, burning, and photophobia.…”
Section: Introductionsupporting
confidence: 52%
“…(6) Similar studies reported the same ocular manifestations. (6,7) A finding related to workers exposed to open-air, wind, and sun using dangerous working tools, as the case of port workers, showed ocular symptoms, such as blurred vision, pruritus, burning, and photophobia. They resulted from foreign bodies; chemical agents, such as acids, alkaline, and detergents; and physical agents, such as acute exposure to optical radiation.…”
Section: Introductionsupporting
confidence: 52%
“…Pterygium is a degenerative lesion of the conjunctiva, which consists of fibro-vascular tissue growing into the cornea. There is strong evidence confirming the connection between chronic UVR exposure and developing a pterygium [15,16]. In the Australian study, which compromised 100 thousands of people, a strong positive correlation between UVR exposure and incidence of pterygium was proved [17].…”
Section: Influence On Conjunctiva and Corneamentioning
confidence: 90%
“…Another study proved that the risk of pterygium was 50-380% higher in outside workers, regardless of latitude [16]. Occupational sun exposure for many hours a day and for many years is such an important risk factor, that it can be called occupational disease [16]. It is worth noticing that wearing a hat, glasses or sunglasses was negatively correlated with pterygium in outside workers [18,19].…”
Section: Influence On Conjunctiva and Corneamentioning
confidence: 99%
See 1 more Smart Citation